Gut dysbiosis and immune dysfunction induced by chronic cola replacement of water in rats: not just a sugar problem - Gao, Huijie; Li, Wanru; Wang, Xin; Ren, Yan; Li, Xiao; Liu, Chao (Frontiers in Nutrition, 2026)
ObjectiveExcessive sugar-sweetened beverage consumption like cola is a worldwide public health problem. However, the effects and mechanisms of replacing water with cola (either as sugar-free cola or sugar-sweetened cola) on intestinal microbiota and overall health remain unknown, prompting this investigation.MethodsTo address this, we created a new experimental model in which cola completely replaced drinking water. Twenty-four Sprague-Dawley rats were randomly divided into three groups (n = 8): water, cola (sugar-sweetened), diet cola, for an 8-week intervention. Body weight, body length, BMI, organ indices, hematological, and serum biochemical parameters, and gut microbiota (16S rRNA gene sequencing) were determined.ResultsBoth colas resulted in immune suppression (lower thymus index and leukopenia) and decreased total protein. The cola group showed renal stress [higher blood urea nitrogen, (BUN)] and a significant increase in spleen index. The diet cola induced a significant transaminases elevation compared to the cola group. Both colas significantly altered intestinal microbiota structure, including changes in diversity and abundance (e.g., shifts in Firmicutes and Bacteroidota proportions and in the abundance of Ligilactobacillus and Lactobacillus). Co-abundance network showed complicated relationships, mostly involving Lactobacillus, Romboutsia, and other taxa. Furthermore, Bacteroidota and unclassified Lactobacillus were significantly correlated with immune organ indices (thymus, spleen) and BUN.ConclusionUsing an innovative model of complete water replacement, our study demonstrates that long-term cola consumption-whether or not sugar containing-has significant perturbative effects on gut microbiota and impairs immune and renal function. These results should warn of the impacts of regular cola intake and the need for further scrutiny of artificial sweeteners.